2019
DOI: 10.1098/rstb.2019.0007
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of female-biased kinship in humans and other mammals

Abstract: Female-biased kinship (FBK) arises in numerous species and in diverse human cultures, suggesting deep evolutionary roots to female-oriented social structures. The significance of FBK has been debated for centuries in human studies, where it has often been described as difficult to explain. At the same time, studies of FBK in non-human animals point to its apparent benefits for longevity, social complexity and reproduction. Are female-biased social systems evolutionarily stable and under what circumstances? Wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…But despite these origins, human behavioral ecologist Eric Smith once observed that “beginning with a problem that seems to lack any profound social dimensions (e.g., prey‐choice, birth spacing, or group size), behavioral ecologists pursue what they hope will be simple answers, only to find that all roads lead to complex social interactions.” 26 In this sense, HBE is a field in which empirical evidence has led to the expansion of practice within the discipline. Compared to early research in the field, recent research on kinship, social support, and intergenerational resource transfers in HBE reflects a much more expansive view of the relevant “environment” that factors into decision‐making: one that includes existing cooperative ties, kinship systems and other social and cultural factors 68–74 …”
Section: The Relationship Between Hbe and Nctmentioning
confidence: 99%
“…But despite these origins, human behavioral ecologist Eric Smith once observed that “beginning with a problem that seems to lack any profound social dimensions (e.g., prey‐choice, birth spacing, or group size), behavioral ecologists pursue what they hope will be simple answers, only to find that all roads lead to complex social interactions.” 26 In this sense, HBE is a field in which empirical evidence has led to the expansion of practice within the discipline. Compared to early research in the field, recent research on kinship, social support, and intergenerational resource transfers in HBE reflects a much more expansive view of the relevant “environment” that factors into decision‐making: one that includes existing cooperative ties, kinship systems and other social and cultural factors 68–74 …”
Section: The Relationship Between Hbe and Nctmentioning
confidence: 99%
“…Such lack of precision fuels the common misconception that it is not possible to define key terms and concepts unambiguously, and in a way that they apply across species (e.g. [18] and other articles in the theme issue). The example above and the preceding discussion show that this is clearly not the case.…”
Section: Lineal Kinship In Cross-specific Perspectivementioning
confidence: 99%
“…Faced with multiple and ambiguous definitions, evolutionarily minded anthropologists have recently taken a pragmatic stance, replacing 'matrilineal kinship' with biologically inspired labels, such as 'female-biased/based/centred kinship' (e.g. [18] and other articles in the theme issue). Underlying this trend is the belief that, if we move past seemingly trivial debates about terminology, we can turn to hypotheses, data and analyses of ever-increasing sophistication.…”
Section: Introductionmentioning
confidence: 99%
“…Exact definitions of post-marital residence patterns vary considerably [12]. Some scholars use "patrilocality" as a general term for residence with or near the husband's family [e.g.…”
Section: Introductionmentioning
confidence: 99%